Ciptakan Pendidikan Nyaman: CSR PLN Peduli Berikan Edukasi Konkret Pencegahan Bullying Sejak Usia Dini Pada Sekolah Sungai Gunung Anyar - Rangga Ardiyansyah; G. Oka Warmana (Pusat Riset dan Inovasi Nasional, 2024)
Bullying is a deliberate act of aggression and degradation by one or a group of people against another individual. These acts of bullying can be physical, verbal, or relational behaviors that aim to hurt, intimidate, or harm others who may be weaker or unable to defend themselves. Bullying can occur anywhere and anytime, when powerful people have the desire to commit acts of violence on people who do not have power. In recent times, cases of bullying have been increasing and grabbing the attention of the community and inviting concerns for safety and comfort in the educational environment. The impact caused by bullying is that the victim has a long trauma, psychological and mental disruption and emotional uncertainty. The educational environment should be a peaceful and comfortable place to support every child in studying and achieving. It is important that we all come together to prevent and solve this bullying problem. This can be realized by providing an understanding of bullying to the impact that occurs on the victim. Therefore, through the PLN Peduli CSR platform, the author conducts community service activities with the aim of providing teaching to prevent bullying cases. This community service activity is carried out in the form of socialization to early childhood in river schools. The methods used are delivering material (lectures), showing animated films, asking questions to children and playing games together. The results to be achieved after this activity are early childhood understanding of the importance of avoiding bullying behavior and understanding the negative impact of bullying. Children are expected to be more concerned about focusing on themselves and be active in efforts to create a comfortable educational environment without bullying. This activity forms an attitude not to do bad habits and always spread kindness among others.